Cell walls of extruded pea snacks: Morphological and mechanical characterisation and finite element modelling. (December 2022) - Jebalia, I.; Della Valle, G.; Guessasma, S.; Kristiawan, M.
Graphical abstract: Reasonable agreement of stress-strain responses was found between the experimental testing (symbols) and fintite element modelling (lines) for pea flour (PF), starch-protein blends (SP), pea protein isolate (PPI) and starch. The mechanical behaviour of composites is governed by their morphology, which displayed protein aggregates (green) dispersed in a starch matrix (grey), in particular, the starch-protein interface index Ii and the volumic fraction of phases presenting different intrinsic properties. Highlights: Composite morphological features were tuned by protein content and extrusion energy. Composite constitutive laws were determined using a bending test and FEM simulation. Particle content decreased composite stress and strain at rupture. Young's modulus and saturation stress were related to the composite interface index. FEM modelling allowed to identify the mechanical effect of structural heterogeneities. Abstract: Pulses extruded foods can be envisaged asall solid foams with voids and walls, the latter being considered as a dense starch/protein composite. Pea flour (PF) and blends of pea starch and pea protein isolate (PPI) with different protein contents (0.5–88% dry basis) were extruded to obtain models of dense starch-protein composites. Their morphology was revealed by CLSM microscopy, and their mechanical properties were investigated using a three-point bending test complemented by Finite Element Method (FEM) modelling. Composite morphology revealed protein aggregates dispersed in the starch matrix. It was described by a starch-protein interface index Ii computed from the measured total area and perimeter of protein aggregates. The mechanical test showed that the extruded PF and PPI ruptured in the elastic domain, while the extruded starch-PPI (SP) blends ruptured in the plasticity domain. The mechanical properties of pea composites were weakened by increasing the particle volume fractions, including proteins and fibres, probably due to the poor adhesion between starch and the other constituents. The mechanical behaviour of pea composites did not accurately follow simple mixing laws because of their morphological heterogeneity. Modelling results show that the elastoplastic constitutive model using the Voce plasticity model satisfactorily described the hardening behaviour of SP blend composites. Reasonable agreement (2–10%) was found between the experimental and modelling approaches for most materials. The computed Young's modulus (1.3–2.5 GPa) and saturation flow stress (20–45 MPa) increased with increasing Ii (0.7–3.1), reflecting the increase of interfacial stiffening with the increase of contact area between starch and proteins. FEM modelling allowed to identify the mechanical effect of structural heterogeneities.